Effects of a nonpeptide motilin receptor antagonist on proximal gastric motor function - Kamerling, Ingrid M C (Blackwell Science Inc, 2004)
AIM: To assess the effects of the motilin receptor antagonist RWJ-68023 on basal and motilin-stimulated proximal gastric volume. METHODS: Eighteen healthy male volunteers received RWJ-68023 in two different doses or placebo for 135 min. After 45 min, subjects received a motilin infusion for 90 min. Proximal gastric volume was measured with a barostat at constant pressure and during isobaric distensions. Abdominal symptoms were scored using visual analogue scales. Motilin and RWJ-68023 concentrations were assessed by radioimmunoassay and liquid chromatography-mass spectrometry, respectively. RESULTS: Both dosages of RWJ-68023 were safe and well tolerated. The most common adverse events were of gastrointestinal origin. RWJ-68023 did not affect basal proximal gastric volume, but the high-dose RWJ-68023 reduced the contractile effect of motilin on the stomach. This antagonizing effect of RWJ-68023 was only significant (P = 0.014) during the distension procedure. CONCLUSIONS: The RWJ-68023 doses used in this study were selected to accomplish plasma concentrations that would block the motilin effect entirely. However, the antagonizing effect of RWJ-68023 was partial and only present when the tonic condition of the stomach was modulated by motilin.